Flood impact on men’s mental health: evidence from flood-prone areas of Bangladesh - Rahman, Md Mostafizur; Shobuj, Ifta Alam; Hossain, Md Tanvir; Alam, Edris; Islam, Md Kamrul; Hossain, Md Kaium (Frontiers in Public Health, 2025)
Disasters can pose significant risks to mental health, often resulting in both temporary and long-lasting psychological distress. This study explores the impact of floods on mental health. A survey was conducted shortly after the 2022 flash flood, in which 452 male participants from the Ajmiriganj and Dharmapasha Upazilas in Bangladesh were surveyed. Mental health was assessed using the DASS-21 instrument, and we examined the variables associated with mental health issues. Descriptive statistics and multiple linear regression analysis were employed. Around 47% of participants reported severe or extremely severe depression, 41% reported severe or extremely severe anxiety, and 36% reported severe or extremely severe stress. Factors such as age, marital status, type of home, occupation, flood safety rating, and property loss during the 2022 flood were all found to be associated with depression. Anxiety was linked to flood safety, occupation, housing type, education level, and marital status. Additionally, all anxiety-related variables were also associated with stress. Mental health issues were more prevalent among older, married, illiterate participants living in kacha (temporary) housing, as well as among agricultural workers and fishers with low safety ratings. Psychological interventions and disaster risk reduction strategies could help mitigate the mental health impact of floods. The findings of this study have important implications for global disaster management and public health.